PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT. TRANS RETAIL - BELLA NURFADILA; TRIANA ANANDA RUSTAM (LP2MTBM MAKARIOZ, 2020)
The main objective in this research is to find out partially and simultaneously the quality of service and promotion ofpurchasing decisions. The population and sample in this study were all customers who visited the Carrefour Kepri MallBatam from January 2019 to December, totaling 70,498 customers who visited. Furthermore, the sample withdrawaltechnique uses a random sample samling. Data collection techniques using a questionnaire questionnaire with a Likert scale.Data analysis with multiple linear regression analysis. The results showed that partially or simultaneously all independentvariables consisting of quality of service and promotion had a positive and significant effect on purchasing decisions atCarrefour Kepri Mall Batam